(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Thyroid function has been extensively evaluated in patients with chronic kidney disease, however the results are variable. Objective:The study was designed to investigate the thyroid dysfunction in uremic patients clinically and biochemically. Methods: The study was conducted in the department of medicine and dialysis unit in AL-Kadhimiya Teaching Hospital in Baghdad. Three groups were taken sixteen patients with end stage renal disease undergoing regular hemodialysis, 22 patients with chronic renal failure treated conservatively and 21 healthy volunteers with no previous history of thyroid disease and their renal function were normal(control group), serum TT3, TT4 and TSH were estimated in all patients and control group by RIA Kits. The results were tabulated and statistically analyzed using Chisequare and t-test. Results:Fifty nine persons included in this study divided into three groups (regular hemodialysis 16, conservative treatment 22 and the control group were 21). Goiter was demonstrated in 12.5% in hemodialysis group, 4.54% of the conservatively treated group. Uremic patients kept on conservative treatment or on regular hemodialysis showed significant reduction of TT3 and TT4 in comparison to the control group, however the level of TSH didn’t show significant alterations, and there were no significant deference in TT3 andTT4 between the patients on conservative management and those maintained on regular hemodialysis. Conclusions:Low TT3 and TT4 are often observed in clinically euthyroid patients with chronic renal failure. These abnormalities do not appear to change significantly after the institution of regular dialysis, on other hand TSH values in clinically euothyroid patients with chronic renal failure were within the normal range, this normal TSH may indicate functional euthyroid status. Key words: Hemodialysis, Chronic renal disease, Triiodothyronin (T3), Thyroxin (T4), Thyroid stimulating hormone (TSH)